The Mental and Physical Burden of Caregiving - Magdalena Stroka (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This study evaluates the mental and physical strain experienced by informal caregivers. Econometric problems due to individuals selecting themselves in to informal care provision are tackled by using informative and detailed data from the largest sick ness fund in Germany and applying propensity score matching techniques. The fi ndings suggest tha t carers take more psychoactive drugs as well as analgesics and gastrointestinal agents. Thus, in formal caregiving appears to be a burdensome task with implications for both mental and physical health.
Keywords: I10; D10; J10; 330